TRUCK STOP FINDER AND MAP APPLICATION: ITS FEATURES AND USAGE - Jaloliddin Elamanov Dilmurod ugli (Journals Park Publishing, 2022)
Looking for a map and truck stop finder application that is user-friendly and can show all the truck stops on the way? Look no further than the truck stop finder app. This app is designed for truck drivers and is user-friendly to find the best route option available.The truck stop finder app can be used to find truck stops by location or by the route. You can also search for truck stops by amenities, such as showers, laundry, and diesel fuel. The truck stop finder app is a must-have for any truck driver.
Keywords: Safety; GPS; map